Production of Kluyveromyces spp. and environmental tolerance induction against Aspergillus flavus - Montemarani, Analía Mariana (2013)
The viability and biomass production of three isolates of Kluyveromyces spp. in six different growth media were studied. All yeast isolates showed good growth in all of the media tested, but nutrient yeast dextrose broth (NYDB 75 %) and molasses soy meal (MSB) media were selected for further analyses. The adaptive response of the yeasts to heat shock and water stress was studied, revealing that 60 min of incubation at 45 °C and a water activity value of 0.95 aw were the appropriate conditions to adapt these yeasts for subsequent analyses. The physiological adaptation did not affect the ecological similarity between biocontrol agents and pathogen. The adapted yeasts also had a negative influence on the growth of Aspergillus flavus RCM89 mycelia and the accumulation of aflatoxin B1 levels in vitro. These results have important implications for optimizing the formulation process of proven biocontrol agents against A. flavus. In addition, the applications of physiological methods are necessary for increasing the performance of biocontrol agents. Moreover, the physiological methods could enhance survival under environmental stress conditions of biological control agents.